Analisis Polisemi Adjektiva Warna dalam Bahasa Rusia - Yoga Adityo Nugroho; Ani Rachmat; Susi Machdalena (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This thesis is entitled “Analysis of Color Adjective Polysemy in Russian". The thesis contains research on polysemy analysis of several colors in the Russian language and explains the use of color adjectives polysemy meaning according to context in sentences. This study uses descriptive qualitative methods by taking primary data sources from the Russian-Indonesian dictionary by Victor Pogadaev (2010) and secondary data from ruscorpora.ru and udarenie.ru. The study was conducted by analyzing what meaning is contained in a color and what nouns can give rise to the meaning in question. The author uses the theories put forward by Russian linguists as a Research Foundation, including Valgina (2003), Rozental (2001), Novikov (2003), Bobrova (1993), Rozental’ et al (2010), Kobozeva (2000), dan Pulkina (1975). The purpose and results of this study will show that color adjectives in the Russian language have many meanings and the use of color polysemous meanings in a sentence.